2016
DOI: 10.1097/iae.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Relation to Ethnicity Measured Using Enhanced Depth Imaging Optical Coherence Tomography

Abstract: Enhanced depth imaging-spectral domain optical coherence tomography is a productive imaging method to study the choroidal thickness. Subfoveal choroidal thickness is not significantly correlated with ethnicity. The study reproduced previously found relations between thinner choroids and longer axial lengths, and increasing myopic refraction and showed no significant associations between subfoveal choroidal thickness and age and sex. Either the right or left eye can be used in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
4
24
2
Order By: Relevance
“…It is not completely clear why the results contradict those found in our population-racial differences are unlikely to be significant, 16 but it may reflect the inclusion of patients with type 1 diabetes and differences in classification of DR. The most plausibly contributory factor is previous photocoagulation; studies including eyes treated with pan retinal photocoagulation (PRP) generally report reduced choroidal thickness in PDR.…”
Section: Discussioncontrasting
confidence: 56%
“…It is not completely clear why the results contradict those found in our population-racial differences are unlikely to be significant, 16 but it may reflect the inclusion of patients with type 1 diabetes and differences in classification of DR. The most plausibly contributory factor is previous photocoagulation; studies including eyes treated with pan retinal photocoagulation (PRP) generally report reduced choroidal thickness in PDR.…”
Section: Discussioncontrasting
confidence: 56%
“…However, it has been demonstrated that subfoveal choroidal thickness does not correlate with ethnicity in patients of ‘white, African and Asian’ descent 12. Along the same line, this study demonstrates that the degree of fundus pigmentation does not necessarily signify choroidal thickness relative to normal.…”
Section: Discussionsupporting
confidence: 51%
“…CTh is known to be thickest at the subfoveal region, with thinning occurring in the nasal and temporal directions [8,9]. Some lesions are known to differentially affect specific regions of the retina, such a reticular pseudodrusen which are most often found in the superior macula [48].…”
Section: Discussionmentioning
confidence: 99%
“…The healthy choroid typically measures 250–400 μm subfoveally [8], with a decrease in thickness in the temporal and nasal directions [8,9]. The relationship between the choroid and cardiovascular disease (CVD) is of particular interest due to its possible use as a biomarker of CVD and in identifying patient cohorts at increased risk for outer retinal disease.…”
Section: Introductionmentioning
confidence: 99%